Salud física en el sistema penitenciario - Muñoz, Iván M. (2020)
This document will provide relevant information on physical health in prison environments, aware that health is an inalienable right of being protection, which protects people deprived of liberty (PPL), both in the field national and global. The legal parameters, guardianship and protection of this right are responsibility of the state, who must comply with the appropriate standards for the treatment, rehabilitation and reintegration of inmates; Therefore, physical health in the prison population, it will be to maintain an adequate lifestyle according to the conditions in which PPL live, as part of guaranteeing Health, it must be detected and diagnose pathologies immediately, this will be possible with a correct organization of spaces, supplies and trained personnel, facilitating care timely medical